Ontogeny of the extrafloral nectaries of Vigna adenantha (Leguminosae, Phaseolae) and its relation with floral development - Ojeda, Fabiana Soledad (2014)
Background: The inflorescences of the genus Vigna Savi have extrafloral nectaries (EFNs) among the flowers whose origin is still unknown. The disposition, anatomy and morphology, as well as the ontogeny of the extrafloral nectaries (EFNs) associated with the inflorescences of Vigna adenantha (G.F.W. Meyer) Maréchal, Mascherpa & Stainier (Leguminosae, Papilionoideae, Phaseolae) were studied. Besides, the ultrastructure of the secretory stage was described. Results: The inflorescence, a raceme, bears a brief globose secondary axis in each node with 2 flowers and 5–7 EFNs, which develop in acropetal direction. Each EFN originates from the abscission of a flower bud that interrupts its development, resulting in an elevated EFN. This secretory structure is formed by a ring of epidermal and parenchymatic cells surrounding a group of elongated central cells. The nectary is irrigated by phloem and xylem. Four developmental stages proceed; each one relates to a different embryological stage of the flowers in each secondary axis. Conclusions: The first functional EFN of each secondary axis of the inflorescence reaches its maturity when both the pollen grains and the embryo sacs are completely developed and the flowers begin to open. The secretion is granulocrine. The following EFNs develop in the same way. Keywords: Extrafloral nectaries Inflorescences Ontogeny Morphology Anatomy Ultrastructure Vigna Leguminosae